ANALISIS KINERJA KEUANGAN PERUSAHAAN BANKKALTIMTARA SEBAGAI SYARAT PENGAJUAN INITIAL PUBLIC OFFERING (IPO) DI BURSA EFEK INDONESIA - Ovigeria Subroto Sinaga (STIE Madani Balikpapan, 2020)
The capital market is one way of obtaining additional capital for a companyto develop its business. One of the things done in the capital market is sellingcompany ownership through the sale of shares. A company must meet certainrequirements in order to sell its initial public offering / IPO to the Indonesian StockExchange (IDX)PT. BPD Kaltim Kaltara (Bankkaltimtara) is one of the largest banksoperating in East and North Kalimantan. This bank has been operating for a longtime and is widely recognized by the public in these two regions. This bank also hasa vision to reach services throughout East Kalimantan and North Kalimantan.The author conducts a financial performance analysis to determine whetherBankkaltimtara can meet the requirements to list its shares on the IDX. In addition,the authors also look at developments in financial performance and conduct ananalysis of trends in financial performance. This is expected to provide an overviewfor us, including potential investors, to assess the performance of Bankkaltimtara.